Relationship between Knowledge, Attitude, and Student Organization to-ward COVID-19 Vaccination Coverage among Pre-Clinical Medical Students - Pratiwi, Dewi; Levani, Yelvi; Nurida, Annisa; Utama, M. Reza (Universitas Muhammadiyah Semarang, 2025)
Background: Refusal to vaccinate is an obstacle to the success of the COVID-19 vaccination program. The community wants health workers to provide insight into the importance of vaccination. Medical students who are often actively involved in community activities directly have a role in the success of the COVID-19 vaccination. This paper examines the relationship between pre-clinical medical student’s knowledge, attitudes, and organization’s history related to COVID-19 vaccination to provide recommendations for behavioral interventions and policies.Objective: To determine the relationship between knowledge, attitude, and organizational history with the coverage of COVID-19 vaccination among respondents.Methods: A cross-sectional online survey of 77 pre-clinical medical students at UM Surabaya using a simple random sampling technique. The questionnaire used belongs to researcher Chyntia Caroline (2021). The research was conducted from August to October 2022. Statistical analysis used SPSSv.26, p<0.05. The Spearman test was performed to determine whether or not there was any relationship between knowledge, attitudes, organization’s history, and COVID-19 vaccination coverage.Results: The level of student knowledge is categorized as ''Sufficient'', and student attitude is classified as ''Good''. The results of the Spearman test found that knowledge and an organization’s history did not affect vaccination coverage (p=0.6 and 0.68). Attitudes affect vaccination coverage (p=0.000).Conclusion: There is no relationship between knowledge and an organization's history. Meanwhile, good attitudes influence COVID-19 vaccination coverage. An awareness campaign should be focused on promoting positive attitudes toward vaccination.